Effect of ascorbic acid and citric acid on bioavailability of iron from Tegillarca granosa via an in vitro digestion/Caco-2 cell culture system. Issue 22 (26th October 2021) - Sun, Bolun; Tan, Beibei; Sun, Nan; Huang, Ping; Hong, Jingxia; Li, Chao; Yang, Wenge
Abstract : Iron deficiency anaemia (IDA) has been receiving worldwide attention. Abstract : Iron deficiency anaemia (IDA) has been receiving worldwide attention. Developing safe and effective iron supplements is of great significance for IDA treatment. Tegillarca granosa ( T. granosa ), a traditional aquaculture bivalve species in China, is considered to be an excellent source of micronutrients, but the distribution and bioavailability of these minerals have yet to be investigated. The present research was conducted to determine the contents and in vitro enzymatic digestibility of minerals in T. granosa, using beef and wheat flour as reference foods. Meanwhile, two iron-binding proteins, hemoglobin and ferritin, were extracted from T. granosa, and their structures, iron accessibility and bioavailability were investigated. Moreover, the effects of ascorbic acid (AA) and citric acid (CA), two commonly applied dietary factors, on these parameters were evaluated. Our results indicated that the mineral levels varied significantly among different food matrices, with T. granosa showing the highest contents of the tested elements. Comparison of iron absorption of meat versus wheat flour and hemoglobin versus ferritin confirmed that heme iron exhibited higher bioavailability than non-heme iron. The addition of the two organic acids notably enhanced the cellular iron uptake of T. granosa -derived proteins. This could be because AA/CA weakened hydrogen bonds within proteins and caused disordered secondary structures, thereby improving their enzymatic digestibility and releasing more soluble iron to be available for absorption. The results of this study provided a basis for the development of T. granosa -derived protein-based iron supplements, promoting the diverse utilization of marine aquatic resources.